2021
DOI: 10.1136/bcr-2020-239207
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor development in mild haemophilia after a major surgery for periampullary cancer (Whipple’s procedure) in an elderly man

Abstract: Around the world, with the availability of factor concentrates, patients with haemophilia have undergone major and minor surgeries. Inhibitor development in early postoperative period leading to inadequate factor recovery and ongoing bleeding is a nightmare for both operating surgeon as well as haematologists. We describe a case of an elderly man with mild haemophilia A, who was diagnosed with pancreatic carcinoma and underwent Whipple’s procedure. After an uneventful procedure, he developed high-titre inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…However, because of the bleeding tendency of hemophiliac patients, physicians might hesitate to perform surgical resection of the liver or even ultrasound‐guided radio frequency ablation (RFA), 10 despite those treatments being indicated. In addition, as these hemophilic patients age, not only hepatic malignancies but also bile duct cancers and pancreatic cancers are developing and requiring surgery if possible 11 . Although some case reports have been published in the abdominal surgical area, no systematic reports have been found in the updated literature 12‐15 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because of the bleeding tendency of hemophiliac patients, physicians might hesitate to perform surgical resection of the liver or even ultrasound‐guided radio frequency ablation (RFA), 10 despite those treatments being indicated. In addition, as these hemophilic patients age, not only hepatic malignancies but also bile duct cancers and pancreatic cancers are developing and requiring surgery if possible 11 . Although some case reports have been published in the abdominal surgical area, no systematic reports have been found in the updated literature 12‐15 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, as these hemophilic patients age, not only hepatic malignancies but also bile duct cancers and pancreatic cancers are developing and requiring surgery if possible. 11 Although some case reports have been published in the abdominal surgical area, no systematic reports have been found in the updated literature. [12][13][14][15] The group of one of the authors reported the results of hepatectomy in hemophilia patients in 2018.…”
Section: Discussionmentioning
confidence: 99%